PENERAPAN AUTHENTIC ASSESSMENT UNTUK MENINGKATKAN SPATIAL ABILITY DAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN GEOGRAFI MATERI HUBUNGAN MANUSIA DAN LINGKUNGAN AKIBAT DINAMIKA HIDROSFER DI KELAS X IPS 1 SMA N 7 SURAKARTA TAHUN AJARAN 2013/2014 - Dewi, Yuli Setyo (Pendidikan Geografi, 2014)
PENERAPAN AUTHENTIC ASSESSMENT UNTUK MENINGKATKAN SPATIAL ABILITY DAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN GEOGRAFI MATERI HUBUNGAN MANUSIA DAN LINGKUNGAN AKIBAT DINAMIKA HIDROSFER DI KELAS X IPS 1 SMA N 7 SURAKARTATAHUN AJARAN 2013/2014 Yuli Setyo Dewi1, Sarwono2, Singgih Prihadi21 Mahasiswa Program Studi Pendidikan Geografi PIPS, FKIP, UNS Surakarta, Indonesia2 Dosen Program Studi Pendidikan Geografi PIPS, FKIP, UNS Surakarta, Indonesia ABSTRACT  The objective of this study is to : (1) find out the increasing of students? spatial ability on Georaphy in human relationship and environment as the effect of hidrosphere dynamics material in X science at Senir High School 7 Surakarta through the implementation of authentic assessment, (2) examine learning outcome of student on Georaphy in human relationship and environment as the effect of hidrosphere dynamics material in X science at Senir High School 7 Surakarta through the implementation of authentic assessment.Research method being implemented in this study was Class Action Research. It was done within 2 cycle and each of them had 4 phases, that was planning, implementation, observation, and reflection. The research subject was 32 students who sit in the X grade of social class in even semester at Senior High Scool 7 Surakarta, 2013/2014 academic year. Data collection technique being used in this study were : observation, documentation, questionnaire, and test. Data analysis technique being implemented was comparative descriptive analysis. The research outcome shows that (1) the implementation of authentic assessment is able for increasing student spatial ability on geography in human relationship and environment as the effect of hidrosphere dynamics material in X social grade at Senir High School 7 Surakarta on the second cycle. This could be seen from the attainment of spatial ability was more than 75%. On the secn cycle the amount f spatial ability were : comparation 84%, heirarki 78%, aura 79%, transition 78%, dan association 86% (2) the implementation of authentic assesment was able for increasing the students learning outcome on geography in human relationship and environment as the effect of hidrosphere dynamics material in X grade social at Senior High School 7 Surakarta on the second cycle. It could be seen from the accession of achievement indicator was more than 75% on the second cycle. The degree of accomplishment of the cognitive learning outcome on the second cycle was 81.25%. The degree of accomplishment of the affective learning outcome on the second cycle was 78.1%. The degree of accomplishment of the psychomotor learning outcome on the second cycle was 93.75%. Keywords : Authentic Assessment, Spatial Ability, Learning Outcome.